2016
DOI: 10.1007/s10909-016-1628-3
|View full text |Cite
|
Sign up to set email alerts
|

Roton Excitations and the Fluid–Solid Phase Transition in Superfluid 2D Yukawa Bosons

Abstract: We compute several groundstate properties and the dynamical structure factor of a 0-temperature system of Bosons interacting with the 2D screened Coulomb (2D-SC) potential. We resort to the exact shadow path-integral ground-state (SPIGS) quantum Monte Carlo method to compute the imaginary-time correlation function of the model, and to the genetic algorithm via falsification of theories (GIFT) to retrieve the dynamical structure factor. We provide a detailed comparison of groundstate properties and collective e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(176 reference statements)
0
6
0
Order By: Relevance
“…We extract the dynamical structure factor from the integral relation F (q, τ ) = e −ωτ S(q, ω)dω. When a parametric model for S(q, ω), and thus F (q, τ ), is reliable, we solve the previous relation with a fit of F (q, τ ), otherwise we use the Genetic Inversion via Falsification of Theories (GIFT) [21,22] algorithm, which is a wellestablished statistical analytic continuation approach [22,23,24,25,26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…We extract the dynamical structure factor from the integral relation F (q, τ ) = e −ωτ S(q, ω)dω. When a parametric model for S(q, ω), and thus F (q, τ ), is reliable, we solve the previous relation with a fit of F (q, τ ), otherwise we use the Genetic Inversion via Falsification of Theories (GIFT) [21,22] algorithm, which is a wellestablished statistical analytic continuation approach [22,23,24,25,26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The GIFT method has been applied to the study of liquid 4 He [28,82,83], 3D hard spheres [67], 2D Yukawa Bosons [84], liquid 3 He [65], 2D soft disks [85,86], the 2D Hubbard model [87] and 1D soft rods [88], in all cases providing very accurate reconstructions of S(q, ω) or the single particle spectral function. Recently [28], we have shown that in 1D, when ω th (q) is known, also the shape close to the frequency threshold can be approximately inferred.…”
Section: Methodsmentioning
confidence: 99%
“…We furthermore see the existence of additional density oscillations around the vortex core, which are themselves expected once a roton minimum is included in the picture. This is a well-known phenomenon [31,33,[38][39][40][41], for which density oscillations are prescribed by the characteristic shape and size of the roton minimum. We represent in the inset of Fig.…”
Section: A Detour Through the Numerical Estimation Of Axisymmetrmentioning
confidence: 99%